Ultralow-friction light-weight water-based paint as well as preparation method and construction method thereof
By introducing raw materials such as epoxy emulsion, conductive filler, structural filler and lightweight filler into the coating, an ultra-low friction lightweight water-based coating is prepared, which solves the difficulty in providing lightweight and multiple protection functions in the prior art. The coating problem achieves efficient multi-function protection effect.
Patent Information
- Application Number
- CN202411657573.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to provide a coating that is both light and has multiple protection functions in the fields of aerospace, precision machinery, etc., especially in application scenarios where frequent friction is required.
A lightweight water-based coating with ultra-low friction is adopted. The raw materials for preparation include epoxy emulsion, conductive filler, structural filler and lightweight filler. Through reasonable proportioning and process treatment, a low friction coefficient and corrosion resistance are formed. , coatings with anti-mold, anti-heat and anti-static properties.
It has achieved a lightweight single coating, which has anti-corrosion, anti-mold, anti-heat, and anti-static properties, and has good friction reduction performance, with a friction coefficient less than 0.08, which is suitable for the protection of high-end equipment.
Smart Images

Figure CN119505637A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of special functional coatings, and in particular to an ultra-low friction lightweight water-based coating and a preparation method and a construction method thereof. Background Art
[0002] In the fields of machinery, electronics, and chemicals, friction and protection issues have always been the focus of research. Traditional protective coating materials mostly focus on single functional protection. However, with the rapid development of modern industry, the performance requirements of special functional coatings in high-end equipment and green manufacturing are becoming higher and higher. For application scenarios that require frequent friction and lightweight, such as aerospace, precision machinery, etc., a coating that is both lightweight and has multiple protective functions is needed to protect it.
[0003] After the coating is applied to the surface of the substrate, a dense protective film can be formed on the surface of the substrate. The coating can be given certain special properties by introducing fillers or pigments with special functions. However, it is often difficult for a single material to have multiple special functional requirements, and the combination of multiple materials may have a certain adverse effect on the comprehensive performance of the coating. Summary of the invention
[0004] In view of this, the object of the present invention is to provide an ultra-low friction lightweight water-based coating and a preparation method and construction method thereof. The coating of the present invention has low friction coefficient, light weight, anti-corrosion, anti-mold, anti-humidity and anti-static properties.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides an ultra-low friction lightweight water-based coating, which comprises the following raw materials by weight: 36-48 parts of film-forming material, 0.8-1.8 parts of dispersant, 0.1-0.3 parts of defoamer, 3-5 parts of conductive filler, 5-10 parts of structural filler, 6-9 parts of lightweight filler, 0.5-1 parts of anti-settling agent, 0.2-0.3 parts of antibacterial agent, 36-42 parts of water, 1-3 parts of cosolvent, and 12-16 parts of curing agent;
[0007] The film-forming substance is epoxy emulsion;
[0008] The conductive filler includes one or more of conductive titanium dioxide, carbon nanotubes and conductive graphite;
[0009] The structural filler includes one or more of barium sulfate and talc;
[0010] The lightweight filler includes one or more of titanium dioxide, silicon dioxide and hollow glass microspheres.
[0011] Preferably, the epoxy emulsion is one or more of HDE8132 epoxy emulsion and JJ20A epoxy emulsion.
[0012] Preferably, the dispersant is one or more of Tech-690 and SP1000P.
[0013] Preferably, the defoaming agent includes one or more of Tech-3810 and Tech-490.
[0014] Preferably, the anti-settling agent is SMP-N aqueous bentonite dilution; the concentration of the SMP-N aqueous bentonite dilution is 3wt%.
[0015] Preferably, the antimicrobial agent is BIOX-ABZ anti-mold additive.
[0016] Preferably, the co-solvent is propylene glycol methyl ether acetate, and the curing agent is a polyamide epoxy resin curing agent.
[0017] The present invention also provides a method for preparing the ultra-low friction lightweight water-based coating described in the above technical solution, comprising the following steps:
[0018] The film-forming substance, the dispersant and the first part of water are first mixed, and then the structural filler and a part of the defoamer are added and second mixed to obtain a pre-mix;
[0019] After grinding the premix, adding a lightweight filler and a conductive filler for a third mixing to obtain a coating slurry;
[0020] The coating slurry, the anti-settling agent, the remaining defoamer, the antibacterial agent, the cosolvent and the second part of water are mixed to obtain a base coating;
[0021] Mixing the curing agent and the third portion of water to obtain a curing agent dilution solution;
[0022] sixthly mixing the base coating and the curing agent diluent to obtain the ultra-low friction lightweight water-based coating;
[0023] The first part of water, the second part of water and the third part of water constitute the water in the ultra-low friction lightweight water-based coating.
[0024] Preferably, after the grinding, the fineness of the obtained material is less than 10 μm.
[0025] The present invention also provides an ultra-low friction lightweight water-based coating as described in the above technical solution or a construction method of the ultra-low friction lightweight water-based coating prepared by the preparation method as described in the above technical solution, comprising the following steps:
[0026] The ultra-low friction lightweight water-based paint is diluted and then applied;
[0027] The viscosity of the coating obtained after dilution is 45-55 KU.
[0028] The invention provides a lightweight water-based coating with ultra-low friction.
[0029] The film-forming material of the present invention is epoxy emulsion, which has strong cohesive force, high mechanical strength and low shrinkage after curing, which helps to maintain the stability of the coating; and the cured epoxy emulsion has good flexibility and can withstand certain deformation without cracking; at the same time, epoxy materials have good chemical stability and can withstand acid, alkali, salt substances, water and heat without damage, thereby improving the corrosion resistance and moisture and heat resistance of the coating. The present invention introduces lightweight fillers to replace part of the structural fillers, thereby reducing the dry film weight of the coating while ensuring the strength, thickness and performance of the coating, and achieving a weight gain of less than 1.5g / μm·m2 per square meter and per micron thickness. The present invention forms a cross-linked conductive path inside the coating through the introduction of conductive fillers, thereby improving the antistatic performance of the coating. After static electricity is generated, it can be quickly discharged through the conductive path inside the coating, avoiding the failure of electronic devices and other dangers caused by the discharge phenomenon caused by static electricity accumulation. The addition of antibacterial agents can give the coating anti-mildew properties. The combination of conductive filler, structural filler and lightweight filler ensures that the obtained coating has the advantages of ultra-low friction, light weight and anti-static properties. The present invention uses water as a diluent, which reduces the atmospheric pollution caused by the volatilization of organic solvents in the coating, has less impact on the environment and human health, is more in line with the environmental protection concept of modern society, and has higher safety during storage, transportation and construction.
[0030] The ultra-low friction lightweight water-based coating provided by the present invention realizes that a single lightweight coating meets the requirements of anti-corrosion, anti-mildew, anti-humidity and anti-static performance. At the same time, the coating has good friction reduction performance. The friction coefficient of the professional cylindrical dual friction is less than 0.08, the coating adhesion is ≤1 level, and the volume resistivity is ≤1×10 9 Ω·cm, salt spray resistance meets the requirement of alternating salt spray for 240h, moisture and heat resistance meets the requirement of 20 cycles without failure, and mildew resistance is ≤ level 1. And according to actual application requirements, the performance can be further improved by adjusting the film-forming material system. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 to Figure 6 The friction performance test results of the coatings of Examples 1 to 6 are as follows;
[0032] Figure 7 to Figure 14 The friction performance test results of the coatings of Comparative Examples 1 to 8 are shown. DETAILED DESCRIPTION
[0033] The present invention provides an ultra-low friction lightweight water-based coating, which comprises the following preparation raw materials in parts by weight:
[0034] 36-48 parts of film-forming substance, 0.8-1.8 parts of dispersant, 0.1-0.3 parts of defoamer, 3-5 parts of conductive filler, 5-10 parts of structural filler, 6-9 parts of lightweight filler, 0.5-1 parts of anti-settling agent, 0.2-0.3 parts of antibacterial agent, 36-42 parts of water, 1-3 parts of cosolvent, 12-16 parts of curing agent;
[0035] The film-forming substance is epoxy emulsion;
[0036] The conductive filler includes one or more of conductive titanium dioxide, carbon nanotubes and conductive graphite;
[0037] The structural filler includes one or more of barium sulfate and talc;
[0038] The lightweight filler includes one or more of titanium dioxide, silicon dioxide and hollow glass microspheres.
[0039] Unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0040] In the present invention, the ultra-low friction lightweight water-based coating includes 36 to 48 parts of the raw material film-forming substance, preferably 39 to 45 parts, and specifically 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47 or 48 parts by weight. In the present invention, the film-forming substance is an epoxy emulsion, and the epoxy emulsion preferably includes one or more of HDE8132 epoxy emulsion and JJ20A epoxy emulsion. In the present invention, when the film-forming substance is a mixture of HDE8132 epoxy emulsion and JJ20A epoxy emulsion, the weight ratio of HDE8132 epoxy emulsion and JJ20A epoxy emulsion in the mixture is preferably 3:2. In a specific embodiment of the present invention, the HDE8132 epoxy emulsion is preferably a product sold by Shanghai Handai Chemical Co., Ltd., and the JJ20A epoxy emulsion is preferably a product sold by Shanghai Junjiang Technology Co., Ltd. In the present invention, the solid content of the epoxy resin is preferably 53+2%. In the present invention, the film-forming substance is selected from epoxy emulsion, which is a water-dispersible emulsion product. The epoxy emulsion is an emulsion with good water dispersibility through the self-emulsification phenomenon of the epoxy resin; the epoxy emulsion has a low viscosity and dispersibility, can participate in the grinding of fillers (including conductive fillers, structural fillers and lightweight fillers), will not cause demulsification failure, and can improve the grinding efficiency.
[0041] In terms of the weight of the film-forming substance, the ultra-low friction lightweight water-based coating includes 0.8 to 1.8 parts of the raw material dispersant, preferably 1 to 1.5 parts, and specifically 0.8 parts, 1 part, 1.2 parts, 1.4 parts, 1.5 parts, 1.6 parts or 1.8 parts. In the present invention, the dispersant is preferably one or more of Tech-690 and SP1000P, and more preferably a mixture of Tech-690 and SP1000P, SP1000P. In the present invention, in the mixture of Tech-690 and SP1000P, the weight ratio of Tech-690 and SP1000P is preferably 1:1. In a specific embodiment of the present invention, the Tech-690 is preferably a product sold by Shanghai Tiger Polymer Technology Co., Ltd., and the SP1000P is preferably a product sold by Guangdong Jindong New Materials Technology Co., Ltd. In the present invention, Tech-690 is a copolymer containing pigment affinity groups, which can deflocculate the filler through the steric hindrance effect, reduce the fineness of the filler particles, thereby improving the gloss and hiding power of the coating, and can reduce the viscosity of the coating and improve the leveling property; SP1000P is an aqueous solution of polyether-modified styrene maleic anhydride copolymer, which can stabilize a variety of fillers, especially has a good dispersing effect on organic pigments and carbon black. The dispersant improves color strength, transparency, gloss and storage stability through the steric stabilization mechanism.
[0042] In terms of the weight percentage of the film-forming substance, the ultra-low friction lightweight water-based coating includes 0.1 to 0.3 parts of the raw material defoamer, specifically 0.1 parts, 0.15 parts, 0.2 parts, 0.25 parts or 0.3 parts. In the present invention, the defoamer preferably includes one or more of Tech-3810 and Tech-490, and more preferably a mixture of Tech-3810 and Tech-490, Tech-3810. In the present invention, in the mixture of Tech-3810 and Tech-490, the weight ratio of Tech-3810 to Tech-490 is preferably 1:1. In the present invention, the Tech-490 is preferably introduced before grinding, and the Tech-3810 is preferably introduced after grinding. In a specific embodiment of the present invention, the defoamer is preferably a product sold by Shanghai Tiger Polymer Technology Co., Ltd. In the present invention, Tech-490 is a vinyl ether copolymer, which should be added under high shear force to prevent the occurrence of shrinkage cavities, and can effectively remove microbubbles in the coating without affecting the transparency or gloss of the high-gloss system; Tech-3810 is a mixture of modified polysiloxane and a bubble-breaking substance, which is added in the paint mixing stage and has a high shear strength to eliminate large bubbles and microbubbles, and can inhibit the generation of construction bubbles.
[0043] In terms of the weight percentage of the film-forming substance, the ultra-low friction lightweight water-based coating includes 3 to 5 parts of the raw conductive filler, specifically 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts. In the present invention, the conductive filler includes one or more of conductive titanium dioxide, carbon nanotubes and conductive graphite, more preferably a mixture of conductive titanium dioxide and conductive graphite, a mixture of conductive graphite and carbon nanotubes, a mixture of conductive titanium dioxide, conductive graphite and carbon nanotubes, and conductive graphite. In the present invention, in the mixture of conductive titanium dioxide and conductive graphite, the weight ratio of conductive titanium dioxide and conductive graphite is preferably 1:1. In the present invention, in the mixture of conductive graphite and carbon nanotubes, the weight ratio of conductive graphite and carbon nanotubes is preferably 7:1. In the present invention, in the mixture of conductive titanium dioxide, conductive graphite and carbon nanotubes, the weight ratio of conductive titanium dioxide, conductive graphite and carbon nanotubes is preferably 2-4:2-3:1, further preferably 4:3:1, specifically 4:3:1, 4.16:3.16:1 or 2:2:1. In a specific embodiment of the present invention, the conductive titanium dioxide is preferably a product sold by Tianjin Jinglin New Materials Technology Co., Ltd., with a production grade of ECP-T; the conductive graphite is preferably a product sold by Shijiazhuang Tonglei Mineral Products Trading Co., Ltd., with a production grade of C-50; the carbon nanotube is preferably a product sold by Shandong Tanfeng New Materials Technology Co., Ltd., with a production grade of TF-210. In the present invention, the average particle size of the ECP-T conductive titanium dioxide is preferably 0.4 μm; the average particle size of the C-50 conductive graphite is preferably 5000 mesh; the diameter of the TF-210 carbon nanotube is preferably 10-20 nm, and the tube length is preferably 5-15 μm. In the present invention, the conductive fillers have different microstructures, specifically: ECP-T conductive titanium dioxide is a spherical material, C-50 conductive graphite is a flake material, and TF-210 carbon nanotubes are tubular materials. The introduction of the three conductive fillers can form a conductive network structure inside the coating, and excellent conductive performance can be achieved at a lower introduction amount. Since the conductive material has a special microstructure, high shear grinding may cause damage to the microstructure and damage to the conductive network, so it should be introduced in the paint mixing stage.
[0044] In terms of the weight of the film-forming substance, the ultra-low friction lightweight water-based coating includes 5 to 10 parts of the raw material structural filler, preferably 6 to 9 parts, more preferably 7 to 8 parts, and specifically 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts. In the present invention, the structural filler includes one or more of barium sulfate and talc, more preferably a mixture of barium sulfate and talc. In the present invention, in the mixture of barium sulfate and talc, the mass ratio of barium sulfate to talc is preferably 5 to 10:2, specifically preferably 5:2, 6:2, 8:2 or 10:2. In the present invention, the barium sulfate is preferably precipitated barium sulfate; the fineness of the precipitated barium sulfate is preferably 3000 mesh. In the present invention, the fineness of the talc is preferably 1250 mesh.
[0045] In terms of the weight percentage of the film-forming substance, the ultra-low friction lightweight water-based coating includes 6 to 9 parts of lightweight fillers as the raw materials for preparation, preferably 7 to 8 parts, and specifically 6 parts, 7 parts, 8 parts or 9 parts. In the present invention, the lightweight filler includes one or more of titanium dioxide, silicon dioxide and hollow glass microspheres, preferably a mixture of titanium dioxide and hollow glass microspheres, a mixture of silicon dioxide and hollow glass microspheres, a mixture of titanium dioxide, silicon dioxide and hollow glass microspheres, and hollow glass microspheres. In the present invention, in the mixture of titanium dioxide and hollow glass microspheres, the weight ratio of titanium dioxide to hollow glass microspheres is preferably 1:6. In the present invention, in the mixture of silicon dioxide and hollow glass microspheres, the weight ratio of silicon dioxide to hollow glass microspheres is preferably 2 to 2.5:5 to 5.5, specifically preferably 2:5 or 2.5:5.5. In the present invention, in the mixture of titanium dioxide, silicon dioxide and hollow glass microspheres, the weight ratio of titanium dioxide, silicon dioxide and hollow glass microspheres is preferably 1:2-3:3-5, specifically preferably 1:2:4, 1:3:5 or 1:2:3. In the present invention, the titanium dioxide is preferably nano titanium dioxide, and the nano titanium dioxide is preferably a product sold by Hubei Huifu Nano Materials Co., Ltd. In the present invention, the silicon dioxide is preferably nano silicon dioxide, and the nano silicon dioxide is preferably a product sold by Shandong Wanhua Tianhe New Materials Co., Ltd. In the present invention, the packing density of the hollow glass microspheres is preferably 0.24-0.28 g / cm 3 .
[0046] In terms of the weight of the film-forming material, the ultra-low friction lightweight water-based coating includes 0.5 to 1 parts of the raw material anti-settling agent, which can be specifically 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1 parts. In the present invention, the anti-settling agent is preferably a SMP-N aqueous bentonite dilution; the concentration of the SMP-N aqueous bentonite dilution is preferably 3wt%. In the present invention, the preparation method of the SMP-N aqueous bentonite dilution preferably includes the following steps: stirring and mixing the SMP-N aqueous bentonite and water, and then swelling to obtain the SMP-N aqueous bentonite dilution; the SMP-N aqueous bentonite is preferably a product of Zhejiang Fenghong New Materials Co., Ltd. In the present invention, the rotation speed of the stirring and mixing is preferably 500r / min, and the present invention does not specifically limit the time of the stirring and mixing, as long as the two can be fully mixed. In the present invention, the swelling time is preferably 12h, and the swelling method is preferably standing. In the present invention, the SMP-N water-based bentonite is a purified and modified high-purity sodium-based montmorillonite clay product, which has high swelling capacity in water and has good thixotropic thickening and suspension properties.
[0047] In terms of the weight of the film-forming substance, the ultra-low friction lightweight water-based paint includes 0.2 to 0.3 parts of the raw antibacterial agent, which can be specifically 0.2 parts, 0.25 parts or 0.3 parts. In the present invention, the antibacterial agent is preferably a BIOX-ABZ antifungal additive. In a specific embodiment of the present invention, the antibacterial agent is preferably a product sold by Shanghai Weiyong Industrial Co., Ltd. In the present invention, BIOX-ABZ is a mixture of inorganic zinc compounds, which can effectively prevent bacterial growth on the paint film.
[0048] The ultra-low friction lightweight water-based coating comprises 36 to 42 parts of raw water, specifically 36, 37, 38, 39, 40, 41 or 42 parts, based on the weight of the film-forming substance. In the present invention, the water is preferably pure water, and the conductivity of the pure water is preferably 0.5±0.3μ s / cm.
[0049] In terms of the weight of the film-forming substance, the ultra-low friction lightweight water-based coating includes 1 to 3 parts of the raw material co-solvent, which can be specifically 1 part, 1.5 parts, 2 parts, 2.5 parts or 3 parts. In the present invention, the co-solvent is preferably propylene glycol methyl ether acetate. Propylene glycol methyl ether acetate is a non-polluting solvent with multiple functional groups. Its molecular structure contains both non-polar and polar parts, and it has a certain solubility for both non-polar and polar substances. Propylene glycol methyl ether acetate is used as a co-solvent to reduce the viscosity of the coating, improve the leveling property, and prolong the drying time of the coating, so as to avoid the coating from drying too quickly, resulting in pores or bubbles in the coating, which affects the friction reduction performance of the coating. In a specific embodiment of the present invention, the co-solvent is a commercially available industrial-grade product.
[0050] The ultra-low friction lightweight water-based coating includes 12 to 16 parts of the raw material curing agent, specifically 12 parts, 13 parts, 14 parts, 15 parts or 16 parts, based on the weight of the film-forming substance. In the present invention, the curing agent is preferably a polyamide epoxy resin curing agent, and the amine value of the polyamide epoxy resin curing agent is preferably 180 to 220 mgKOH / g. In a specific embodiment of the present invention, the curing agent is preferably a product produced by Yitailong (Tianjin) Synthetic Materials Co., Ltd., with a production grade of 2115.
[0051] The present invention also provides a method for preparing the ultra-low friction lightweight water-based coating described in the above technical solution, comprising the following steps:
[0052] The film-forming substance, the dispersant and the first part of water are first mixed, and then the structural filler and a part of the defoamer are added and second mixed to obtain a pre-mix;
[0053] After grinding the premix, adding a lightweight filler and a conductive filler for a third mixing to obtain a coating slurry;
[0054] The coating slurry, the anti-settling agent, the remaining defoamer, the antibacterial agent, the cosolvent and the second part of water are mixed to obtain a base coating;
[0055] Mixing the curing agent and the third portion of water to obtain a curing agent dilution solution;
[0056] Mixing the base coating and the curing agent diluent to obtain the ultra-low friction lightweight water-based coating;
[0057] The first part of water, the second part of water and the third part of water constitute the water in the ultra-low friction lightweight water-based coating.
[0058] In the present invention, the film-forming substance, the dispersant and the first part of water are first mixed, and then the structural filler and a part of the defoamer are added and secondly mixed to obtain the pre-mix.
[0059] In the present invention, the first mixing is preferably performed under stirring conditions, and the stirring speed is preferably not higher than 1000 r / min, more preferably 500 to 1000 r / min, and more preferably 600 to 800 r / min.
[0060] In the present invention, the addition rate of the structural filler is preferably 2 parts / minute. In the present invention, the partial defoamer is preferably Tech-490.
[0061] In the present invention, the second mixing is preferably performed under stirring conditions, and the stirring speed is preferably not higher than 1000 r / min, more preferably 500 to 1000 r / min, and more preferably 600 to 800 r / min.
[0062] In the present invention, the stirring speed of the first mixing and the second mixing is controlled to be no higher than 1000 r / min, so as to avoid demulsification of the film-forming material due to grinding.
[0063] After obtaining the premix, the present invention grinds the premix, adds a lightweight filler and a conductive filler, and performs a third mixing to obtain a coating slurry.
[0064] In the present invention, the grinding beads used in the grinding are preferably zirconium dioxide microbeads, and the diameter of the zirconium dioxide microbeads is preferably 0.6-0.8 mm. In the present invention, the rotation speed of the grinding is preferably 800-1000 r / min, and the grinding time is preferably 2.5 h. In the present invention, cooling water is preferably used during the grinding process to control the material temperature to be no higher than 50°C. In the present invention, after the grinding, the fineness of the obtained material is preferably less than 10 μm.
[0065] In the present invention, the lightweight filler and the conductive filler are not ground during the preparation process. Since the lightweight filler is a nano-scale powder or a hollow structure, the grinding process may cause the lightweight filler to break and fail, affecting the lightweight performance of the coating; the conductive filler may cause the spherical or needle-shaped structure to break or break after grinding, causing damage to the conductive structure, thereby affecting the conductive performance.
[0066] After obtaining the coating slurry, the present invention fourthly mixes the coating slurry with the anti-settling agent, the remaining defoamer, the antibacterial agent, the cosolvent and the second part of water to obtain the base coating.
[0067] In the present invention, the remaining defoaming agent is preferably Tech-3810. In the present invention, the fourth mixing is preferably performed under stirring, the stirring speed is preferably 800 r / min, and the time is preferably 30 min.
[0068] After the fourth mixing, the present invention preferably further comprises filtering, and the filtration preferably uses an 80-mesh filter cloth.
[0069] The present invention mixes the curing agent and the third part of water fifthly to obtain a curing agent dilution solution.
[0070] In the present invention, the mass ratio of the curing agent to the third part of water is preferably 1:1.
[0071] In the present invention, the fifth mixing is preferably performed under stirring conditions, and the stirring speed is preferably 500 r / min.
[0072] After obtaining the base coating and the curing agent dilution, the present invention mixes the base coating and the curing agent dilution to obtain the ultra-low friction lightweight water-based coating.
[0073] In the present invention, the base slurry and the curing agent dilution are preferably mixed before use.
[0074] The present invention also provides an ultra-low friction lightweight water-based coating as described in the above technical solution or a construction method of the ultra-low friction lightweight water-based coating prepared by the preparation method as described in the above technical solution, comprising the following steps:
[0075] The ultra-low friction lightweight water-based paint is diluted and then applied.
[0076] In the present invention, the diluting agent is preferably water, and the viscosity of the coating obtained after the dilution is 45 to 55 KU.
[0077] In the present invention, the construction is preferably completed within 2 to 3 hours.
[0078] The ultra-low friction lightweight water-based coating provided by the present invention and its preparation method and construction method are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the scope of protection of the present invention.
[0079] Example 1
[0080] 21.6 parts by weight of HDE8132 epoxy emulsion, 14.4 parts by weight of JJ20A epoxy emulsion, 1.8 parts by weight of Tech-690 dispersant, and 10 parts by weight of pure water (conductivity ≤ 1.0 μs / cm) were added to a mixing tank and mixed evenly at a stirring speed of 800 r / min; then 4 parts by weight of precipitated barium sulfate and 1 part by weight of talcum powder were slowly added to the mixing tank at a speed of 2 parts by weight / min, and mixed evenly at a stirring speed of 800 r / min to obtain a pre-mix.
[0081] Use zirconium dioxide microbeads with a size of 0.6 to 0.8 mm, use a sand mill to grind at a grinding speed of 800 r / min for 2 hours, control the material temperature to be less than 50°C, and grind to a fineness of <10 μm; at a speed of 600 r / min, slowly add 5 parts by weight of conductive graphite, 1 part by weight of nano titanium dioxide, and 6 parts by weight of hollow glass microbeads, mix well, and obtain a coating slurry.
[0082] 3 parts by weight of SMP-N and 97 parts by weight of water were added into a mixing tank and mixed evenly at a speed of 500 r / min. After mixing evenly, the mixture was allowed to stand for 12 hours until the aqueous bentonite was completely swollen, thereby obtaining a SMP-N dilution solution.
[0083] Add 0.2 parts by weight of Tech-3810, 0.5 parts of SMP-N diluent, 0.2 parts by weight of BIOX-ABZ mildew inhibitor, 2 parts by weight of propylene glycol methyl ether acetate, and 15 parts by weight of pure water (conductivity ≤ 1.0 μs / cm) to the coating slurry, disperse at a speed of 800 r / min for 20 minutes, and filter with 80-mesh filter cloth to obtain a base coating.
[0084] 12 parts of polyamide epoxy resin curing agent and 12 parts of pure water (conductivity ≤ 1.0 μs / cm) were added into a mixing tank and mixed evenly at a rotation speed of 500 r / min to obtain a curing agent dilution solution.
[0085] During use, mix the base paint with the curing agent diluent, use water to adjust the paint viscosity to 45KU, and obtain a constructible paint product; after spraying it onto the sample surface, wait for it to dry completely to obtain an ultra-low friction, lightweight water-based four-proof coating.
[0086] Example 2
[0087] 28.8 parts by weight of HDE8132 epoxy emulsion, 19.2 parts by weight of JJ20A epoxy emulsion, 1.5 parts by weight of SP1000P dispersant, and 10 parts by weight of pure water (conductivity ≤ 1.0 μs / cm) were added to a mixing tank and mixed evenly at a stirring speed of 1000 r / min; then 8 parts by weight of precipitated barium sulfate and 2 parts by weight of talcum powder were slowly added to the mixing tank at a speed of 2 parts by weight / min, and 0.2 parts by weight of Tech-490 defoamer was added, and the mixture was mixed evenly at a stirring speed of 1000 r / min to obtain a pre-mix.
[0088] Use zirconium dioxide microbeads with a size of 0.6 to 0.8 mm, use a sand mill to grind at a grinding speed of 1000 r / min for 3 hours, control the material temperature to be less than 50°C, and grind to a fineness of <10 μm; at a speed of 400 r / min, slowly add 3.5 parts by weight of conductive graphite, 0.5 parts by weight of carbon nanotubes, 2 parts by weight of nano-silicon dioxide, and 5 parts by weight of hollow glass microbeads, mix well, and obtain a coating slurry.
[0089] 3 parts by weight of SMP-N and 97 parts by weight of water were added into a mixing tank and mixed evenly at a speed of 500 r / min. After mixing evenly, the mixture was allowed to stand for 12 hours until the aqueous bentonite was completely swollen, thereby obtaining a SMP-N dilution solution.
[0090] Add 0.6 parts of SMP-N diluent, 0.3 parts by weight of BIOX-ABZ mildew inhibitor, 2 parts by weight of propylene glycol methyl ether acetate, and 10 parts by weight of pure water (conductivity ≤ 1.0 μs / cm) to the coating slurry, disperse at a speed of 1000 r / min for 40 minutes, and filter with 80-mesh filter cloth to obtain a base coating.
[0091] 16 parts of polyamide epoxy resin curing agent and 16 parts of pure water (conductivity ≤ 1.0 μs / cm) were added into a mixing tank and mixed evenly at a rotation speed of 500 r / min to obtain a curing agent dilution solution.
[0092] During use, mix the base paint with the curing agent diluent, use water to adjust the paint viscosity to 55KU, and obtain a constructible paint product; after spraying it onto the sample surface, wait for it to dry completely to obtain an ultra-low friction, lightweight water-based four-proof coating.
[0093] Example 3
[0094] 23.4 parts by weight of HDE8132 epoxy emulsion, 15.6 parts by weight of JJ20A epoxy emulsion, 0.6 parts by weight of Tech-690 dispersant, 0.6 parts by weight of SP1000P dispersant, and 10 parts by weight of pure water (conductivity ≤ 1.0 μs / cm) were added to a mixing tank and mixed uniformly at a stirring speed of 600 r / min; then 5 parts by weight of precipitated barium sulfate and 2 parts by weight of talcum powder were slowly added to the mixing tank at a speed of 2 parts by weight / min, and 0.1 parts by weight of Tech-490 defoamer was added, and the mixture was mixed uniformly at a stirring speed of 600 r / min to obtain a pre-mix.
[0095] Use zirconium dioxide microbeads with a size of 0.6 to 0.8 mm, use a sand mill to grind at a grinding speed of 800 r / min for 2.5 hours, control the material temperature to be less than 50°C, and grind to a fineness of <10 μm; at a speed of 600 r / min, slowly add 2 parts by weight of conductive titanium dioxide, 1.5 parts by weight of conductive graphite, 0.5 parts by weight of carbon nanotubes, 1 part by weight of nano titanium dioxide, 2 parts by weight of nano silicon dioxide, and 4 parts by weight of hollow glass microbeads, mix well, and obtain a coating slurry.
[0096] 3 parts by weight of SMP-N and 97 parts by weight of water were added into a mixing tank and mixed evenly at a speed of 500 r / min. After mixing evenly, the mixture was allowed to stand for 12 hours until the aqueous bentonite was completely swollen, thereby obtaining a SMP-N dilution solution.
[0097] Add 0.1 parts by weight of Tech-3810 defoamer, 1 part by weight of SMP-N diluent, 0.25 parts by weight of BIOX-ABZ mildew inhibitor, 1 part by weight of propylene glycol methyl ether acetate, and 15 parts by weight of pure water (conductivity ≤ 1.0 μs / cm) to the coating slurry, disperse at a speed of 800 r / min for 30 minutes, and filter with 80-mesh filter cloth to obtain a base coating.
[0098] 13 parts of polyamide epoxy resin curing agent and 13 parts of pure water (conductivity ≤ 1.0 μs / cm) were added into a mixing tank and mixed evenly at a rotation speed of 500 r / min to obtain a curing agent dilution solution.
[0099] During use, mix the base paint with the curing agent diluent, use water to adjust the paint viscosity to 50KU, and obtain a constructible paint product; after spraying it onto the sample surface, wait for it to dry completely to obtain an ultra-low friction, lightweight water-based four-proof coating.
[0100] Example 4
[0101] 27 parts by weight of HDE8132 epoxy emulsion, 18 parts by weight of JJ20A epoxy emulsion, 0.5 parts by weight of Tech-690 dispersant, 0.5 parts by weight of SP1000P dispersant, and 10 parts by weight of pure water (conductivity ≤ 1.0 μs / cm) are added to a mixing tank and mixed uniformly at a stirring speed of 600 r / min; then 5 parts by weight of precipitated barium sulfate and 2 parts by weight of talcum powder are slowly added to the mixing tank at a speed of 2 parts by weight / min, and mixed uniformly at a stirring speed of 600 r / min to obtain a pre-mix.
[0102] Use 0.6N0.8mm zirconium dioxide microbeads and use a sand mill to grind at a grinding speed of 800r / min for 2.5h, control the material temperature to be less than 50°C, and grind to a fineness of <10μm; at a speed of 600r / min, slowly add 1.5 parts by weight of conductive titanium dioxide, 1.5 parts by weight of conductive graphite, 1 part by weight of nano titanium dioxide, 3 parts by weight of nano silicon dioxide, and 5 parts by weight of hollow glass microbeads, mix well, and obtain a coating slurry.
[0103] 3 parts by weight of SMP-N and 97 parts by weight of water were added into a mixing tank and mixed evenly at a speed of 500 r / min. After mixing evenly, the mixture was allowed to stand for 12 hours until the aqueous bentonite was completely swollen, thereby obtaining a SMP-N dilution solution.
[0104] Add 0.3 parts by weight of Tech-3810 defoamer, 0.6 parts by weight of SMP-N diluent, 0.25 parts by weight of BIOX-ABZ mildew inhibitor, 3 parts by weight of propylene glycol methyl ether acetate, and 13 parts by weight of pure water (conductivity ≤1.0μs / cm) to the coating slurry, disperse at a speed of 800r / min for 30 minutes, and filter with 80-mesh filter cloth to obtain a base coating.
[0105] 15 parts of polyamide epoxy resin curing agent and 15 parts of pure water (conductivity ≤ 1.0 μs / cm) were added into a mixing tank and mixed evenly at a rotation speed of 500 r / min to obtain a curing agent dilution solution.
[0106] During use, mix the base paint with the curing agent diluent, use water to adjust the paint viscosity to 50KU, and obtain a constructible paint product; after spraying it onto the sample surface, wait for it to dry completely to obtain an ultra-low friction, lightweight water-based four-proof coating.
[0107] Example 5
[0108] 42 parts by weight of HDE8132 epoxy emulsion, 0.8 parts by weight of Tech-690 dispersant, and 10 parts by weight of pure water (conductivity ≤ 1.0 μs / cm) were added to a mixing tank and mixed evenly at a stirring speed of 500 r / min; then 6 parts by weight of precipitated barium sulfate and 2 parts by weight of talcum powder were slowly added to the mixing tank at a speed of 2 parts by weight / min, and 0.3 parts by weight of Tech-490 defoamer was added, and the mixture was mixed evenly at a stirring speed of 500 r / min to obtain a pre-mix.
[0109] Use zirconium dioxide microbeads with a size of 0.6 to 0.8 mm, use a sand mill to grind at a grinding speed of 1000 r / min for 3 hours, control the material temperature to be less than 50°C, and grind to a fineness of <10 μm; at a speed of 600 r / min, slowly add 2.5 parts by weight of conductive titanium dioxide, 1.9 parts by weight of conductive graphite, 0.6 parts by weight of nano titanium dioxide, 1 part by weight of nano titanium dioxide, 2 parts by weight of nano silicon dioxide, and 3 parts by weight of hollow glass microbeads, mix well, and obtain a coating slurry.
[0110] 3 parts by weight of SMP-N and 97 parts by weight of water were added into a mixing tank and mixed evenly at a speed of 500 r / min. After mixing evenly, the mixture was allowed to stand for 12 hours until the aqueous bentonite was completely swollen, thereby obtaining a SMP-N dilution solution.
[0111] Add 1 part by weight of SMP-N diluent, 0.25 part by weight of BIOX-ABZ mildew inhibitor, 2 parts by weight of propylene glycol methyl ether acetate, and 15 parts by weight of pure water (conductivity ≤ 1.0 μs / cm) to the coating slurry, disperse at a speed of 800 r / min for 30 minutes, and filter with 80-mesh filter cloth to obtain a base coating.
[0112] 14 parts of polyamide epoxy resin curing agent and 14 parts of pure water (conductivity ≤ 1.0 μs / cm) were added into a mixing tank and mixed evenly at a rotation speed of 500 r / min to obtain a curing agent dilution solution.
[0113] During use, mix the base paint with the curing agent diluent, use water to adjust the paint viscosity to 50KU, and obtain a constructible paint product; after spraying it onto the sample surface, wait for it to dry completely to obtain an ultra-low friction, lightweight water-based four-proof coating.
[0114] Example 6
[0115] 42 parts by weight of JJ20A epoxy emulsion, 1 part by weight of Tech-690 dispersant, and 10 parts by weight of pure water (conductivity ≤ 1.0 μs / cm) were added to a mixing tank and mixed evenly at a stirring speed of 600 r / min; then 5 parts by weight of precipitated barium sulfate and 1 part by weight of talcum powder were slowly added to the mixing tank at a speed of 2 parts by weight / min, and mixed evenly at a stirring speed of 600 r / min to obtain a pre-mix.
[0116] Use zirconium dioxide microbeads with a size of 0.6 to 0.8 mm, use a sand mill to grind at a grinding speed of 800 r / min for 3 hours, control the material temperature to be less than 50°C, and grind to a fineness of <10 μm; at a speed of 600 r / min, slowly add 2 parts by weight of conductive titanium dioxide, 2 parts by weight of conductive graphite, 1 part by weight of carbon nanotubes, 2.5 parts by weight of nano-silicon dioxide, and 5.5 parts by weight of hollow glass microbeads, mix well, and obtain a coating slurry.
[0117] 3 parts by weight of SMP-N and 97 parts by weight of water were added into a mixing tank and mixed evenly at a speed of 500 r / min. After mixing evenly, the mixture was allowed to stand for 12 hours until the aqueous bentonite was completely swollen, thereby obtaining a SMP-N dilution solution.
[0118] Add 0.1 parts by weight of Tech-3810 defoamer, 0.5 parts by weight of SMP-N diluent, 0.2 parts by weight of BIOX-ABZ mildew inhibitor, 3 parts by weight of propylene glycol methyl ether acetate, and 18 parts by weight of pure water (conductivity ≤1.0μs / cm) to the coating slurry, disperse at a speed of 800r / min for 30 minutes, and filter with 80-mesh filter cloth to obtain a base coating.
[0119] 14 parts of polyamide epoxy resin curing agent and 14 parts of pure water (conductivity ≤ 1.0 μs / cm) were added into a mixing tank and mixed evenly at a rotation speed of 500 r / min to obtain a curing agent dilution solution.
[0120] During use, mix the base paint with the curing agent diluent, use water to adjust the paint viscosity to 50KU, and obtain a constructible paint product; after spraying it onto the sample surface, wait for it to dry completely to obtain an ultra-low friction, lightweight water-based four-proof coating.
[0121] Table 1 Coating formula of Examples 1 to 6
[0122]
[0123]
[0124] Table 2 Coating formulas of comparative examples 1 to 8
[0125]
[0126]
[0127] Performance Testing
[0128] The coating thickness of the embodiment and the comparative example was controlled at 55±5 μm.
[0129] The coating adhesion test of the embodiment and the comparative example was conducted according to GB / T 9286-2021 "Scratch test for paints and varnishes"; the weight gain test was calculated based on the substrate area, substrate weight, coating weight after drying, and coating thickness to obtain the weight per mm. 3 , the weight added per μm of coating.
[0130] In the moisture and heat resistance test of the coatings in the embodiments and comparative examples, a high and low temperature alternating test chamber is used, and the relative humidity is controlled at 95±5%. The temperature is raised from 30°C to 60°C in the first 2 hours, the temperature is stabilized at 60°C for 2 to 8 hours, the temperature is reduced from 60°C to 30°C for 8 to 16 hours, and stabilized at 30°C for 16 to 24 hours; each 24 hours is one cycle, and a total of 10 cycles are tested; it is required that the coating has no bubbling, peeling, etc.
[0131] In the corrosion protection performance test of the coatings in the embodiments and comparative examples, a neutral salt spray corrosion test chamber was used, the test temperature was controlled at 35±2°C, the salt solution concentration was 5±1%, the pH value was 6.5-7.2, and the salt spray deposition amount was 1-3mL / h; spraying was performed for 24 hours and drying was performed for 24 hours; one cycle was 48 hours, and a total of 3 cycles were tested; the coating was required to have no blistering, wrinkling, cracking, or peeling except for local edges, and no corrosion of the base metal occurred.
[0132] In the test of the anti-mildew performance of the coating in the embodiments and comparative examples, fungus group 1 (including: Aspergillus niger, Aspergillus terreus, Penicillium variotii, Penicillium funiculum, Trichoderma viride, Penicillium ochregreenii, and Scopulariopsis brevis) was used, the test temperature was controlled at 30±1°C, the humidity was 70%, and the test time was 28 days; it was required that there was little or no mold growth on the surface of the coating material.
[0133] In the antistatic performance test of the coating in the embodiment and the comparative example, a resistivity meter was used for testing; the coating was sprayed on the surface of a 100×100×0.5mm copper plate, the inner diameter of the test fitting was 50mm, the outer diameter was 60mm, the test voltage was 100V, and the power-on time was 60s; the volume resistivity of the coating was required to be no more than 109Ω·cm.
[0134] In the friction performance test of the coatings in the embodiments and comparative examples, a friction and wear testing machine was used, a PTFE cylinder with a diameter of 16 mm was selected as the dual surface, a rotation radius of 19.1 mm, a rotation speed of 15 rpm, a load of 12 N, and a test time of 3 min; the coating friction coefficient was required to be no greater than 0.08.
[0135] The specific results are shown in Tables 3 and 4. Figure 1 to Figure 14 .
[0136] Table 3 Coating test results of Example 16
[0137]
[0138]
[0139] Table 4 Coating test results of Comparative Examples 1 to 8
[0140] Test items Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Coating thickness / μm 55.3 55.7 54.9 56.3 56.1 55.8 56.0 54.8 <![CDATA[Weight gain / g / μm·m 2 > 1.843 1.367 1.744 2.044 1.104 2.312 1.626 1.975 Moisture and heat resistance normal normal normal normal normal normal normal normal Anti-corrosion properties No corrosion No corrosion No corrosion No corrosion No corrosion No corrosion No corrosion No corrosion Anti-mold performance Level 0 Level 0 Level 0 Level 0 Level 0 Level 0 Level 0 Level 0 Volume resistivity / Ω·cm <![CDATA[8.44×10 6 ]]> <![CDATA[2.46×10 10 ]]> <![CDATA[3.54×10 4 ]]> <![CDATA[5.56×10 5 ]]> <![CDATA[7.24×10 7 ]]> <![CDATA[8.42×10 8 ]]> <![CDATA[4.25×10 11 ]]> <![CDATA[6.57×10 8 ]]>
[0141] Figure 1 to Figure 6 The friction performance test results of the coatings of Examples 1 to 6 are shown in order. Figure 1 to Figure 6 It can be seen that: during the repeatability verification process, the friction coefficient of the coating is stable within 0.8, and the friction coefficient will show a gradual downward trend as the friction time increases. The main reason is that the friction is mainly static friction in the early stage, which will cause the friction coefficient to increase; after the movement starts, as the friction time increases, the coating flatness gradually improves, which helps to reduce the friction coefficient. In order to improve the friction reduction effect of the coating throughout its life cycle, Examples 1 to 6 embodied in the present invention can stabilize the friction coefficient within 0.8 in a short period of time.
[0142] Figure 7 to Figure 14 The friction performance test results of the coatings of Comparative Examples 1 to 8 are shown in order. Figure 7 to Figure 14 It can be seen that the proportion of pigments and fillers (including conductive fillers, structural fillers and lightweight fillers) in the coating has a certain influence on the friction coefficient of the coating. Increasing the amount of functional pigments and fillers can improve their targeted functional performance, but increasing the amount of pigments and fillers (including conductive fillers, structural fillers and lightweight fillers) will lead to a decrease in the smoothness of the coating, thereby affecting the surface flatness of the coating, which is indirectly reflected in an increase in the friction coefficient.
[0143] The four anti-corrosion properties of the coatings of Examples 1 to 6 were tested. The thickness of the coatings of Examples 1 to 6 was 55±5 μm. After 10 cycles of moisture and heat resistance test, the coatings had no bubbling or peeling. After 3 salt spray cycles, the coatings had no bubbling, wrinkling, cracking or peeling, and the base metal did not corrode. After 28 days of testing, the anti-mildew performance of the coatings of Examples 1 to 6 met the requirements of a Class 0 anti-mildew agent. After the anti-static performance test of the coatings of Examples 1 to 6, the volume resistivity of the coatings was less than 1×10 9 Ω·cm.
[0144] By testing the weight gain performance of the coatings of Examples 1 to 6, the weight gain of the coatings of Examples 1 to 6 is 1.345 to 1.461 g / μm·m 2 The weight gain per square meter and per micron thickness is less than 1.5g, which has good weight reduction performance. By testing the friction performance of the coatings of Examples 1 to 6, the average friction coefficients of the coatings of Examples 1 to 6 are all less than 0.08, which have good friction reduction performance.
[0145] The coatings of comparative examples 1 to 8 were tested for performance. In comparative example 1, when the amount of structural filler increased, the weight of the coating per unit area was significantly increased, the conductivity decreased, and the friction coefficient increased; in comparative example 2, when the amount of conductive filler decreased, the conductivity of the coating decreased significantly, and due to the decrease in the pigment-to-base ratio, the friction coefficient of the coating decreased; in comparative example 3, when the amount of conductive filler increased, the conductivity of the coating increased significantly, but the friction coefficient increased significantly; in comparative example 4, when the amount of lightweight filler decreased, the weight of the coating per unit area was significantly increased, and the friction coefficient decreased; in comparative example 5, when the amount of lightweight filler increased, the weight of the coating per unit area was significantly decreased, and due to the large oil absorption of the lightweight filler, the friction coefficient increased significantly; in comparative example 6, when the structural filler selected heavy calcium carbonate instead of precipitated barium sulfate, the weight of the coating per unit area was significantly increased; in comparative example 7, after conductive mica was used as a conductive filler, the conductivity of the coating decreased significantly; in comparative example 8, after lightweight perlite was used as a lightweight filler, the weight of the coating per unit area was increased.
[0146] According to the results of the performance test examples, it is shown that the ultra-low friction lightweight water-based four-proof coating prepared by the present invention has good friction reduction performance and anti-corrosion, anti-humidity and heat, anti-mildew and anti-static properties, and through the introduction of lightweight materials, the coating has good weight reduction performance.
[0147] It can be seen from the above examples that the ultra-low friction, lightweight, water-based, four-proof coating provided by the present invention has good environmental performance and lightweight performance, and has both friction reduction and four-proof functions. The preparation of a multifunctional integrated composite performance coating product is realized, which can meet the special protection requirements in a variety of complex service environments. The product preparation process is simple and convenient for large-scale application production.
[0148] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An ultra-low friction lightweight water-based coating, characterized in that: The preparation raw materials include the following in parts by weight: 36-48 parts of film-forming substance, 0.8-1.8 parts of dispersant, 0.1-0.3 parts of defoamer, 3-5 parts of conductive filler, 5-10 parts of structural filler, 6-9 parts of lightweight filler, 0.5-1 parts of anti-settling agent, 0.2-0.3 parts of antibacterial agent, 36-42 parts of water, 1-3 parts of cosolvent, and 12-16 parts of curing agent; The film-forming substance is epoxy emulsion; The conductive filler includes one or more of conductive titanium dioxide, carbon nanotubes and conductive graphite; The structural filler includes one or more of barium sulfate and talc; The lightweight filler includes one or more of titanium dioxide, silicon dioxide and hollow glass microspheres.
2. The ultra-low friction lightweight water-based paint according to claim 1, characterized in that: The epoxy emulsion is one or more of HDE8132 epoxy emulsion and JJ20A epoxy emulsion.
3. The ultra-low friction lightweight water-based paint according to claim 1, characterized in that: The dispersant is one or more of Tech-690 and SP1000P.
4. The ultra-low friction lightweight water-based paint according to claim 1, characterized in that: The defoaming agent includes one or more of Tech-3810 and Tech-490.
5. The ultra-low friction lightweight water-based paint according to claim 1, characterized in that: The anti-settling agent is SMP-N aqueous bentonite dilution; the concentration of the SMP-N aqueous bentonite dilution is 3wt%.
6. The ultra-low friction lightweight water-based paint according to claim 1, characterized in that: The antimicrobial agent is BIOX-ABZ anti-mildew additive.
7. The ultra-low friction lightweight water-based paint according to claim 1, characterized in that: The cosolvent is propylene glycol methyl ether acetate, and the curing agent is a polyamide epoxy resin curing agent.
8. The method for preparing the ultra-low friction lightweight water-based coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: The film-forming substance, the dispersant and the first part of water are first mixed, and then the structural filler and a part of the defoamer are added and second mixed to obtain a pre-mix; After grinding the premix, adding a lightweight filler and a conductive filler for a third mixing to obtain a coating slurry; The coating slurry, the anti-settling agent, the remaining defoamer, the antibacterial agent, the cosolvent and the second part of water are mixed to obtain a base coating; Mixing the curing agent and the third portion of water to obtain a curing agent dilution solution; sixthly mixing the base coating and the curing agent diluent to obtain the ultra-low friction lightweight water-based coating; The first part of water, the second part of water and the third part of water constitute the water in the ultra-low friction lightweight water-based coating.
9. The preparation method according to claim 8, characterized in that: After the grinding, the fineness of the obtained material is less than 10 μm.
10. A construction method for the ultra-low friction lightweight water-based paint according to any one of claims 1 to 7 or the ultra-low friction lightweight water-based paint prepared by the preparation method according to any one of claims 8 to 9, characterized in that: The following steps are involved: The ultra-low friction lightweight water-based paint is diluted and then applied; The viscosity of the coating obtained after dilution is 45-55 KU.
Citation Information
Patent Citations
Anticorrosive paint and preparation method thereof
CN104403496A
Ultralow-density environment-friendly flame-retardant abradable seal coating material and use method thereof
CN114032007A
Lubricating, wear-reducing and noise-reducing coating as well as preparation method and application thereof
CN115403987A